Sound attenuation and preferred music in the treatment of problem behavior maintained by escape from noise. Issue 3 (6th June 2018) - Kettering, Tracy L.; Fisher, Wayne W.; Kelley, Michael E.; LaRue, Robert H.
Abstract : We examined the extent to which different sounds functioned as motivating operations (MO) that evoked problem behavior during a functional analysis for two participants. Results suggested that escape from loud noises reinforced the problem behavior for one participant and escape from arguing reinforced problem behavior for the other participant. Noncontingent delivery of preferred music through sound‐attenuating headphones decreased problem behavior without the use of extinction for both participants. We discuss the results in terms of the abolishing effects of the intervention.